Design and impact of the national workshop for early career geoscience faculty. Issue 4 (1st October 2020) - Beane, Rachel J.; Altermatt, Ellen R.; Iverson, Ellen R.; Macdonald, R. Heather
Abstract: The National Association of Geoscience Teachers' Workshop for Early Career Geoscience Faculty: Teaching, Research, and Managing One's Career has been offered annually since 1999. The five-day workshop with accompanying web resources employs a "whole faculty" approach to support geoscience faculty members during their transition into academic careers. More than 1, 000 faculty members (53% female, 47% male) have attended the national workshop; 52% from doctoral-granting institutions, 15% master's, 28% bachelor's, and 5% associates. Evidence-based instructional practices are shared and modeled during workshop sessions. Situated learning theory grounds the workshop design and promotes the development of a community of practice. Examination of the 2016 National Geoscience Faculty Survey data using univariate analyses of covariance (ANCOVAs) showed that workshop alumni report spending more class time on student activities, questions, and discussion than faculty members who did not participate in the workshop, particularly on small group discussions or think-pair-share and in-class exercises (for introductory courses p < . 05; for majors courses p < .001). Workshop alumni also were more likely than faculty who did not participate to report feeling part of a geoscience community that shares their goals, philosophy, and values for geoscience education ( p < .01), more likely to report that interactions with this community help them to become better educators ( p < .001), and more likely to attend talks on teaching methods or science education ( p < .001). Although causality cannot be established without random assignment, these findings are consistent with the hypothesis that this discipline-based workshop with its holistic approach is effective at promoting evidence-based teaching strategies and a community of practice.